Effects of the P‐Glycoprotein Inhibitor Clarithromycin on the Pharmacokinetics of Intravenous and Oral Trospium Chloride: A 4‐Way Crossover Drug‐Drug Interaction Study in Healthy Subjects. (11th April 2019) - Abebe, Bayew Tsega; Weiss, Michael; Modess, Christiane; Roustom, Tarek; Tadken, Tobias; Wegner, Danilo; Schwantes, Ulrich; Neumeister, Claudia; Schulz, Hans‐Ulrich; Scheuch, Eberhard; Siegmund, Werner
Abstract: The quaternary ammonium compound trospium chloride is poorly absorbed from 2 "absorption windows" in the jejunum and cecum/ascending colon, respectively. To confirm whether intestinal P‐glycoprotein (P‐gp) is involved, a 4‐period, crossover drug interaction study with trospium chloride after intravenous (2 mg) and oral administration (30 mg) without and after comedication of clarithromycin (500 mg), an inhibitor for P‐gp, was initiated in 12 healthy subjects. Pharmacokinetics of trospium was evaluated using gas chromatography–mass spectrometry, noncompartmental evaluation, and pharmacokinetic modeling. Trospium chloride was poorly absorbed after oral administration (absolute bioavailability, ∼8%–10%). About 30% of the bioavailable dose fraction was absorbed from the "narrow window". Comedication with clarithromycin increased steady‐state distribution volumes by ∼27% ( P < .01). Bioavailability was not increased as hypothesized. The geometric mean ratios (90% confidence interval) for area under the plasma concentration–time curve, maximum concentration, and renal clearance accounted for 0.75 (0.56–1.01), 0.64 (0.45–0.89), and 1.00 (0.90–1.13), respectively. The amount of trospium absorbed from the "narrow window" was reduced in all subjects but from the "wider window" in only 9 of them. Bioavailability was strongly predicted by the maximum absorption rate of trospium in the distal "window" (rs 2 = 0.910, P < .0001). In conclusion, the P‐gp inhibitor clarithromycin significantly increases distribution volumes but not oral absorption of trospium. The amount absorbed from the "narrow window" was lowered in all subjects. However, the extent of all influences seems not to be of clinical relevance.